Educational practices in China, Korea, and the United States : reflections from a study abroad experience - Wang, Chuang (College teacher); Kolano, Lan; Kim, Do-Hong (Language, literacy, and learning., 2019)
This book is written by a diverse cohort of both of American educators, including professors, teachers, school counselors, and school administrators from pre-K to college levels. Most of the contributors come from disciplinary areas of English as a second language and school administration. With the pressure of Common Core State Standards Initiative, American educators are now shifting their focus to standards-based instruction. Meanwhile, Chinese educators are moving away from national standards and developing state level curriculum and instruction to meet specific needs of the students in local provinces. There is also a debate about whether or not to use the National College Entrance Examination as the only test for college admission. Some provinces (e.g., Zhejiang and Hubei) are administering their own college entrance examinations. The book outlines the sociocultural roots of education in the three countries, linking the tradition and philosophical orientations to each country's own history of education. Furthermore, the book compares and contrasts the curriculum, especially the teaching of English as a second/foreign language, in three countries.This book examines the stress of students, physical education, various pedagogical styles in foreign language education as well as instructional texts and cross-cultural dialogue between teachers. Additionally, the book explores factors that influence parent's involvement and women's educational and career aspirations. Lastly, the book presents modern technologies such as smart learning technologies and online learning platforms not only to facilitate future educational systems but also to promote international exchanges.The chapters of the book are thematically diverse, but they help to provide inspirations for educators both in American and Asian countries. The findings offer alternative practical lenses for educational community to seek for some "middle ground" between Chinese, South Korea and American education. The intended audience for this book is graduate students, teachers, administrators, and professionals in education.